SAT0601 Incidence of Serious Infections in Patients with Rheumatoid Arthritis and Spondyloarthritis Exposed To a-TNF Therapy. Results from Biobadabrasil Registry. (15th July 2016) - Ranza, R.; Laurindo, I.; Titton, D.; Bertolo, M.; Bianchi, W.; Brenol, C.; Carvalho, H.; Castro, G.; Cecconi, M.; Costa, I.; Duarte, A.; Fernandes, V.; et al.
Abstract : Background: The safety profile of biologic drugs might have substantial regional differences. Since 2009, the Brazilian Society of Rheumatology runs BiobadaBrasil, a registry for monitoring of biologic therapies in rheumatic diseases, in collaboration with other Latin America countries (BiobadaAmerica) and with Biobadaser Objectives: To report the incidence of serious infectious adverse events (SIAE) in Rheumatoid Arthritis (RA) and Spondyloarthritis (SpA) patients exposed to biologic a-TNF drugs in Brazil Methods: BiobadaBrasil counts on thirty two centers, from almost all Brazilian states, that prospectively include patients with active rheumatic diseases who started a biologic drug or a synthetic DMARD as a parallel control group. A constant three level monitory of data quality is maintained (online, by phone and "in situ"). This study focuses on SIAE (for definition: Protocolo 1.1 at https://biobadaser.ser.es/biobadamerica/Brasil/cgi-bin/upload/documentacion.aspx ) in RA and SpA (Ankylosing Spondylitis+Psoriatic Arthritis) patients exposed to a-TNFs from January 2009 to June 2015. Time of exposure was set from start of the drug to the date of last administration or censorship. Continuous variables were expressed as mean with standard deviation (SD). SAE incidence rate was calculated per 1000 patient/years with 95%CI Results: 1601 subjects with RA (1024) and SpA (577) exposed to a-TNF drugs were included in BiobadaBrasil, 6298 p/y, follow-up 2.9 (2.3) yrs, 65% females, at baseline: age 52 (12.5) yrs, disease duration 8.6 (8) yrs. Controls were 572 (RA 528, SpA 44), 2093 p/y, follow-up 3.6 (2.2) yrs, 90% females, at baseline: age 55 (13) yrs, disease duration 5.3 (7.3) yrs. The incidence rates of SIAE were: a-TNF RA & SpA 35 [30, 40] vs controls 15 [10, 21], ratio 2.34 [1.6, 3.5] p<0.001, a-TNF RA 43 [37, 50] vs a-TNF SpA 21 [16, 28], ratio 0.5 [0.36, 0.69] p<0.001. Subsequent a-TNF was associated with a higher incidence of SIAE when compared with first (ratio 1.6 [1.17, 2.17], p=0.0013). When only RA patients were considered, incidence ratio between a-TNFs and controls raised to 3.11 [2.06, 4.86] p<0.001 and Adalimumab comes out as the a-TNF with a lower incidence of SIAE, 29 [22, 39] vs Infliximab 55 [43, 70], ratio 0.53 [0.35, 0.79] p=0.0006, with no statistical difference between Etanercept 48 [37, 62] and Infliximab, ratio 0.87 [0.6, 1.26] p=0.22. In both groups, a-TNF and controls, respiratory and urinary tracts serious infections accounted for 2/3 of all events, followed by skin/soft tissues and osteo articular and SIAE were not statistically associated with age, disease duration or corticosteroid use Conclusions: In BiobadaBrasil registry, patients exposed to a-TNF drugs had an incidence rate of serious infections 2-fold that of the control group, significantly lower in SpA than in RA. Acknowledgement: for data monitoring P Cabral, for contributing to BiobadaBrasil registry, L.Barbosa, W.Chahade, A.Hayata, A.Kakehasi, M.Pinheiro, A.Ranzolin, M.Scheinberg, F.Sztajnbok, I.Silveira Disclosure of Interest: None declared